Higher triglyceride glucose-waist height ratio index is associated with higher prevalence of gallstone: a population-based study - Wang, Jianjun; Chen, Sirui; Chen, Xi; Qin, Chuan; Hu, Junchao; Zeng, Xintao; Luo, Hua; Yang, Pei; Luo, Huiwen; Yuan, Chuanpeng; Shi, Ruizi; Wang, Decai (Frontiers in Medicine, 2024)
Background The aim of this study is to evaluate the association between triglyceride glucose-waist height ratio (TyG-WHtR) index and the prevalence of gallstone disease (GSD), alongside the age at first gallstone surgery among adult populations within the United States. Methods We screened participants using the National Health and Nutrition Examination Survey (NHANES). Logistic regression analysis, generalized additive modeling, smoothed curve fitting, and subgroup analysis were employed to assess the association between the TyG-WHtR index, prevalence of GSD, and the age at initial gallstone surgical intervention. Results In this study, 3,728 participants were enrolled, among whom 395 individuals reported a prior history of GSD. The association between the TyG-WHtR index and the prevalence of GSD demonstrated a non-linear, positive association. After adjusting for all potential confounders, for each incremental unit rise in the TyG-WHtR index, there was a 47% escalation in the prevalence of GSD (OR = 1.47, 95% CI: 1.29, 1.68). Subgroup analyses indicated a more pronounced association between the TyG-WHtR index and the prevalence of GSD among individuals aged 20–80 years, females, non-Hispanic white population, non-Hispanic black population, other racial groups, and non-diabetic cohorts. Additionally, this study identified that the TyG-WHtR index may be negatively correlated with age at first surgical treatment of gallstones. Conclusion An elevated TyG-WHtR index demonstrates a positive association with the prevalence of GSD. However, more prospective studies are needed to validate our findings.